The association between antibiotics and community-associated Staphylococcus aureus colonization in the United States population: Analysis of the National Health and Nutrition Examination Survey (NHANES). Issue 45 (11th November 2022) - Chen, Baixing; Li, Shaoshuo; Lin, Shi; Huang, Mingling; Dong, Hang
Abstract : Staphylococcus aureus nasal colonization is a seriously opportunistic infection. However, there is a lack of research of relationship between antibiotics and S aureus colonization in the general population. Through a cross-sectional investigation, this study intends to establish the parameters related to S aureus nasal colonization, specifically the function antibiotics play in colonization. The key information from 2001 to 2004 was abstracted from National Health and Nutrition Examination Survey (NHANES), including information on general demographics, health care status, antibiotic prescription, diabetes, alcohol consumption, and tobacco smoke exposure. The participants colonized with methicillin-susceptible S aureus (MSSA), or methicillin-resistant S aureus (MRSA) were defined as the case group, and the control group was subjects without positive S aureus colonization. Univariate and multivariate logistic regression models were used to identify the variables associated with MSSA and MRSA colonization. The records of 18, 607 individuals were included, involving 13, 205 cases without S aureus colonization, 5195 cases with MSSA, and 207 cases with MRSA. In the multivariate logistic regression analysis, the risk of MSSA colonization was significantly reduced with fluoroquinolone use (75% risk reduction, P = .02), sulfonamide use (98% risk reduction, P < .01), tetracycline use (81% risk reduction, P < .01) and antibiotic combination therapy (risk reduction 76%, P < .01). Female, race and total household size were strongly associated with MSSA carriage. On the other hand, regarding MRSA colonization, fluoroquinolone use, long-term care, and former smoker were positively associated with MRSA colonization, while high income was negatively associated with MRSA colonization. More proper use of broad-spectrum antibiotics contributes to reducing MSSA colonization. Former smokers should also practice better personal hygiene to limit the possibility of MRSA colonization.